Implementation of Obligation to Give Parking Tickets in Parking Regulation in Surabaya City - Kasih, Kiki Darma; Pratami, Risti (Riwayat: Educational Journal of History and Humanities, 2024)
Indonesia's increasing population, supported by rapid growth of motorized vehicles, poses serious challenges related to traffic congestion and environmental impacts. Geographical factors and economic growth reinforce this trend, especially in large cities such as Surabaya. However, slow road infrastructure development causes severe congestion. This study aims to describe the implementation of the obligation to provide parking tickets in accordance with Surabaya City Regional Regulation number 3 of 2018 in Surabaya City. This study uses a descriptive qualitative method using Jan Merse's theory and indicators. Data were collected through interviews, observations, and documentation. The results show that the information conveyed by the government and related agencies is quite good through social and print media. However, improvements are still needed in socialization and training to ensure good service to parking service users. In addition, the implementation of the contents of the Regional Regulation policy has not been optimal, especially regarding supervision and proof. Public support for this policy is quite good, but a review of several articles is needed to improve its effectiveness. Coordination between the government, private sector, and the community is the key to the success of implementing this policy. This study concludes that despite progress, there is still room for improvement in the implementation of parking policies in Surabaya City.